Shifting Terms and Concepts: From Defence to (Human) Security - Marsili, M. (XII Portuguese Congress of Sociology (XXII APS), 2023)
keep a person, building, or country safe from danger or crime". These definitions show how the nature of the concept of security is changing, incorporating that of defence into much broader domains than the military realm. The term "defence", is given as a synonym of "security" by the majority of these dictionaries (Merriam-Webster, Cambridge, Oxford, Collins), even though Britannica and Macmillan continue to be anchored to the dichotomy of defence/external and security/internal, respectively, by providing the words "national security" and "internal security", is evidence of this trend. The evolving concept of security must be scrutinised, with special attention paid to the notion of human security, boosted by UN General Assembly resolution 66/290 and the NATO Strategic Concept 2022, and currently under investigation by the Exploratory Team of the NATO Science and Technology Organization.